2021
DOI: 10.3390/jcm10132792
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 and Cytomegalovirus Co-Infections—A Case Series of Critically Ill Patients

Abstract: The SARS-CoV-2 pandemic has placed great strain on the most developed of health care systems, especially in the context of critical care. Although co-infections with cytomegalovirus (CMV) are frequent in the critically ill due to underlying immune suppression of multiple causes, the impact on COVID-19 patients remains unclear. Furthermore, severe COVID-19 has recently been associated with significant immune suppression, and this may in turn impact CMV reactivation, possibly contributing to clinical course. Nev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 11 publications
0
18
0
Order By: Relevance
“…Although co‐infections with CMV are frequent in critically ill patients, but the impact on COVID‐19 patients is unclear. Moniz et al 4 presented five case reports of CMV reactivation in COVID‐19 patients admitted to the ICU with respiratory failure. It was well described that critical or severe illness can induce immune suppression.…”
Section: Discussionmentioning
confidence: 99%
“…Although co‐infections with CMV are frequent in critically ill patients, but the impact on COVID‐19 patients is unclear. Moniz et al 4 presented five case reports of CMV reactivation in COVID‐19 patients admitted to the ICU with respiratory failure. It was well described that critical or severe illness can induce immune suppression.…”
Section: Discussionmentioning
confidence: 99%
“…Moniz et al [ 9 ] presented a case series of five patients coinfected with cytomegalovirus (CMV) admitted to the intensive care unit due to respiratory failure related to COVID-19. The authors speculate that the reason for the reactivation was the immunosuppression possibly associated with COVID-19.…”
Section: Clinical Picturementioning
confidence: 99%
“…Years later, persistent HCMV infection might be considered a potential risk factor exacerbating age-associated diseases and immunosenescence which is defined as the age-associated deterioration in overall immune condition (12)(13)(14) although some studies have indicated that the link between HCMV and immune aging is obscure (3,15). Further, various stimuli can induce HCMV reactivation; it might be triggered in SARS-CoV-2 infected patients (16,17) thus exacerbating the risk of coronavirus disease 2019 (COVID-19) (18,19). Even if this interaction is still elusive and additional large scale studies are recommended (16), CMV testing and treatment should be taken into consideration in such critical conditions (18).…”
Section: Introductionmentioning
confidence: 99%
“…Further, various stimuli can induce HCMV reactivation; it might be triggered in SARS-CoV-2 infected patients (16,17) thus exacerbating the risk of coronavirus disease 2019 (COVID-19) (18,19). Even if this interaction is still elusive and additional large scale studies are recommended (16), CMV testing and treatment should be taken into consideration in such critical conditions (18). CMV status must be taken into account for several vaccine responses, especially cancer despite the use of HCMV-based therapeutic cancer vaccines (20), since it has been suggested that with advanced age and due to CMV-associated altered immunity in both healthy and immunocompromised hosts, vaccine immunogenicity was modulated (21)(22)(23).…”
Section: Introductionmentioning
confidence: 99%